Demographic patterns of two related desert shrubs with overlapping distributions in response to past climate changes - Yu, Qiushi; Hu, Jing; Hu, Xiaoke; Zhou, Yongfeng; Wang, Fanglin; Jiang, Shengxiu; Wang, Yuqi (Frontiers in Plant Science, 2024)
Numerous studies have revealed that past geological events and climatic fluctuations had profoundly affected the genetic structure and demographic patterns of species. However, related species with overlapping ranges may have responded to such environmental changes in different ways. In this study, we compared the genetic structure and population dynamics of two typical desert shrubs with overlapping distributions in northern China, Nitraria tangutorum and Nitraria sphaerocarpa, based on chloroplast DNA (cpDNA) variations and species distribution models. We sequenced two cpDNA fragments (trnH-trnA and atpH-atpI) in 633 individuals sampled from 52 natural populations. Twenty-four chlorotypes, including eight rare chlorotypes, were identified, and a single dominant haplotype (H4) widely occurred in the entire geographical ranges of the two species. There were also a few distinctive chlorotypes fixed in different geographical regions. Population structure analyses suggested that the two species had significantly different levels of total genetic diversity and interpopulation differentiation, which was highly likely correlated with the special habitat preferences of the two species. A clear phylogeographic structure was identified to exist among populations of N. sphaerocarpa, but not exist for N. tangutorum. The neutral tests, together with the distribution of pairwise differences revealed that N. tangutorum experienced a sudden demographic expansion, and its expansion approximately occurred between 21 and 7 Kya before present, while a rapid range expansion was not identified for N. sphaerocarpa.The ecological niche modeling (ENM) analysis indicated that the potential ranges of two species apparently fluctuated during the past and present periods, with obvious contraction in the Last Glacial Maximum (LGM) and recolonization in the present, respectively, comparing to the Last Interglacial (LIG). These findings suggest that the two species extensively occurred in the Northwest of China before the Quaternary, and the current populations of them originated from a few separated glacial refugia following their habitat fragmentation in the Quarternary. Our results provide new insights on the impact of past geological and climatic fluctuations on the population dynamics of desert plants in northwestern China, and further enforce the hypothesis that there were several independent glacial refugia for these species during the Quaternary glaciations.